Pengaruh Agresivitas Pelaporan Keuangan terhadap Agresivitas Pajak: Dampak Penerapan Mandatory Disclosure Rules (Studi pada Negara-negara Anggota G-20) - Rezza Regia Sugandi; Ida Farida Adi Prawira (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2019)
This study aims to examine the effect of the aggressiveness of financial reporting on tax aggressiveness behavior and examine the differences in tax aggressiveness behavior between before and after the implementation of mandatory disclosure rules. This study used data sourced from the financial statements of companies listed on investing.com for the 2016-2017 period. The samples used were 54 companies. The data analysis method used descriptive statistical analysis using panel data regression. The results showed that the aggressiveness of financial reporting affected the tax aggressiveness and there was no difference in the behavior of tax aggressiveness between before and after the implementation of mandatory disclosure rules.